Improving children's cognitive modifiability by dynamic assessment in 3D Immersive Virtual Reality environments - David Passig; David Tzuriel; Ganit Eshel-Kedmi (Pensa MultiMedia, 2016)
Increasing evidence reveals the efficacy of dynamic assessment (DA) procedure in providing rich and reliable feedback regarding children's cognitive modifiability. The DA procedure included four phases: pre-teaching test, teaching, post-teaching and transfer test two weeks after teaching. The teaching phase includes mediated learning experience strategies. Children's cognitive modifiability was examined by pre- to post-teaching improvement and by the transfer test. Children in Grades 1 and 2 (n ¼ 117) were randomly assigned into three experimental groups and one control group. Each of the experimental groups was given the teaching phase in a different modality: 3D Immersive Virtual Reality (IVR, n ¼ 36), 2D (n ¼ 36), and tangible blocks (TB, n ¼ 24). The control group (n¼ 21) was not given teaching phase. The teaching phase included strategies of solving problems from the Analogies Subtest of the Cognitive Modifiability Battery (CMB). Pre- and post-teaching CMB Analogies tests were administered to all groups followed by CMB Transfer Analogies two weeks later. The findings indicate that the 2D and TB groups showed higher cognitive modifiability than the control group. Also, the findings indicate that teaching in a 3D IVR environment contributed to the children's cognitive modifiability more than in the other groups in the CMB Transfer Analogies. The findings are discussed in relation to the unique enhancing characteristics of the 3D IVR condition combined with the applied mediation strategies.